KEANEKARAGAMAN JENIS TUMBUHAN OBAT-OBATAN DAN PEMANFAATANNYA BERDASARKAN PENGETAHUAN MASYARAKAT LOKAL DI KECAMATAN MALINAU UTARA KABUPATEN MALINAU KALIMANTAN TIMUR - Purity Sabila Ajiningrum (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2017)
The objective of the study was to know local knowledge system of Dayak people in East Kalimantan. The data was collected using interview method to gather all information on plant diversity and it usage by the local society based on their own perception. The interview is using purposive sampling technique, conducted on the local society respondents whether male or female with a lifespan of 18 years or older. The number of respondents is 20% of the people in every sub district who took the Non Timber Forest Products (NTFPs) in the forest. The result of this research showed that many local people have a good knowledge about diversity surround them. Based on the results of interview, there were 31 plants species which were used as medication by the people. The factors relating to the cultural significance of plants would be discussed in detail in this article. Keywords: Timber Forest Products (NTFPs), Index of Cultural Significance (ICS), local society, interview